The utility of the reperfusion rate of tissue oxygen saturation as a measure of vascular endothelial function in adolescents: reliability, validity and sensitivity - Kranen, Sascha H.; Oliveira, Ricardo S.; Bond, Bert; Williams, Craig A.; Barker, Alan R. (Frontiers in Physiology, 2023)
The near-infrared spectroscopy (NIRS)-derived reperfusion rate of tissue oxygen saturation (slope 2 StO2) may provide a surrogate measure of vascular function, however, this has yet to be examined in a paediatric population.This study investigated in adolescents: 1) the between-day reliability of NIRS-derived measurements; 2) the relationship between slope 2 StO2 and macro-(flow-mediated dilation, FMD) and microvascular (peak reactive hyperaemia PRH) function; and 3) the effect of highintensity interval exercise (HIIE) on slope 2 StO2, FMD, and PRH.Nineteen boys (13.3 ± 0.5 y) visited the laboratory on two occasions, separated by ~ 1 week.On visit 1, participants underwent simultaneous assessment of brachial artery FMD and slope 2 StO2 and PRH on the internal face of the forearm. On visit 2, participants completed a bout of HIIE with slope 2 StO2, FMD and PRH measured pre-, immediately post-and 1.5 hours post-exercise.Slope 2 StO2 showed no mean bias (P = 0.18) and an intraclass correlation coefficient of 0.67 (P = 0.003) between visits. No significant correlation between slope 2 StO2 and FMD or PRH was observed on visit 1 (r = -0.04, P = 0.89 and r = -0.30, P = 0.23, respectively) or visit 2 preexercise (r = -0.28, P = 0.25 and r = -0.31, P = 0.20, respectively). Compared to pre-exercise, FMD decreased immediately post-exercise (P < 0.001) and then increased 1.5 hours postexercise (P < 0.001). No significant change was detected for slope 2 StO2 (P = 0.30) or PRH (P = 0.55) following HIIE.In adolescents, slope 2 StO2 can be measured reliably, however, it is not correlated with FMD or PRH and does not follow the acute time course of changes in FMD post-exercise. Hence, the use of slope 2 StO2 as a surrogate measure of vascular function in youth must be refuted.